Perumahan Arbain sebagai Bentuk Pengurangan Stigma Sosial Terhadap Janda di Pasuruan - Ameilia Ning Ayunisa (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2022)
This study aims to determine how the role of Arbain housing in changing the stigma of widows in society. This is because there are many pros and cons that arise regarding the stigma of a person who is a widow in society. Talking about widows, it is inseparable from the existing structure in society. The structure of Indonesian society still adheres to the patrnarchic culture, which is the concept that men hold power over all important roles in society and basically women are deprived of access to this power so that the balance of power actually beneﬁts men. This belief causes the role of women in society to be discriminated against or given priority. Meanwhile men hold power over all important roles that exist in society. Women in this regard feel unfairly treated. Seeing this, many programs support women to develop their potential and help reduce stigma against widows through this arbain housing program. is an effort to increase the abilities, skills, attitudes, and change the stigmatization of society so that they do not only look at women who are single parents one eye